Academics' perceptions of the benefits and challenges of self and peer assessment in higher education. Issue 2 (17th February 2018) - Adachi, Chie; Tai, Joanna Hong-Meng; Dawson, Phillip
Abstract: Despite compelling evidence of its potential effectiveness, uptake of self and peer assessment in higher education has been slower than expected. As with other assessment practices, self and peer assessment is ultimately enabled, or inhibited, by the actions of individual academics. This paper explores what academics see as the benefits and challenges of implementing self and peer assessment, through the analysis of interviews with 13 Australian academics. Thematic analysis of our qualitative data identified seven themes of benefits and five challenges. Our academics showed strong belief in the power of self and peer assessment as formative assessment, contrary to past literature which has focussed on the accuracy of students' marking. This paper therefore brings insights as to not only what academics value about self and peer assessment but also identifies potential inhibitors in practice. Recommendations are made about improving the design and implementation of self and peer assessment in higher education.